A surface modified manganese-based lithium iron phosphate positive electrode material and preparation method thereof

Through surface modification technology, the multi-doped carbon composite is fully mixed with the preparation raw materials of lithium manganese iron phosphate to form a multi-doped carbon composite doped with fluorine, sodium, and silver elements, and is wrapped in a manganese-based lithium iron phosphate precursor. In terms of body, the problem of insufficient conductivity and Li+ diffusion capacity of LMP cathode materials is solved, and its electrochemical performance and safety are significantly improved.

CN119208577BActive Publication Date: 2025-02-11HUNAN YUNENG NEW ENERGY BATTERY MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411688842.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-11
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

The conductivity of manganese-based lithium iron phosphate (LMP) cathode material has a low electrical conductivity and limited Li+ diffusion ability, which seriously restricts its commercial application.

Method used

Through surface modification technology, the multi-doped carbon composite and the preparation raw material of lithium manganese iron phosphate are fully mixed to form a multi-doped carbon composite doped with fluorine, sodium, and silver elements, wrapped in a manganese-based lithium iron phosphate precursor. On the body, a carbon encapsulation layer and a silver skeleton are formed to enhance the electrochemical properties of the material.

Benefits of technology

The electrochemical performance of manganese-based lithium iron phosphate cathode material is significantly improved, including improving conductivity and Li+ diffusion capabilities, improving charge and discharge performance and rate performance, and enhancing the structural stability and safety of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208577B_ABST
    Figure CN119208577B_ABST
Patent Text Reader

Abstract

The invention discloses a surface-modified manganese-based lithium iron phosphate positive electrode material and a preparation method thereof, and relates to the technical field of lithium ion batteries. The material comprises the following components in parts by weight: 95-100 parts of raw materials for preparing lithium manganese iron phosphate, and 2-3 parts of a multinary doped carbon composite; the multinary doped carbon composite is doped with fluorine, sodium and silver elements; the silver nitrate in the multinary doped carbon composite forms a network-like silver skeleton inside a carbon coating layer, and sodium fluoride is attached to the surface of the silver skeleton; after the multinary doped carbon composite is pyrolyzed, the formation of the carbon coating layer is not completed, so in the subsequent carbonization process, the formed carbon layer will bury the silver skeleton, and the silver skeleton is located inside the carbon layer, and the surface of the carbon layer still presents a smooth carbon layer; the internal silver skeleton can improve the strength of the carbon coating layer on the one hand, and prevent manganese ions from escaping; on the other hand, the resistance of silver is extremely small, which can reduce the adverse effect of the carbon layer on the impedance of the positive electrode material, thereby improving its electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a surface-modified manganese-based lithium iron phosphate positive electrode material and a preparation method thereof. Background Art

[0002] With the rapid development of the new energy industry, lithium-ion batteries, as key devices for energy storage and conversion, have great significance for electric vehicles, energy storage systems and other fields. Lithium iron phosphate (LiMnPO4, LMP) cathode materials have become a hot research topic in the field of lithium-ion batteries due to their high safety, low cost and good environmental friendliness. However, the conductivity of LMP materials is low. + The limited diffusion capacity seriously restricts its commercial application. In order to overcome these difficulties, surface modification technology has emerged to improve the electrochemical performance of LMP materials by changing the external characteristics or internal structure of the materials.

[0003] Manganese-based lithium iron phosphate cathode material has an olivine structure, in which Li + It can only diffuse in one dimension along the 010 direction of the plane, and the charge transfer mainly occurs on the 010 plane, resulting in an extremely low lithium ion diffusion coefficient. In addition, the electrical conductivity of LMP materials is also relatively low, which further limits its charge and discharge performance and rate performance. Therefore, how to improve the electrical conductivity and Li + Diffusion capacity has become the focus of current research.

[0004] Based on this, the present invention is devoted to a surface-modified manganese-based lithium iron phosphate positive electrode material and a preparation method to improve the electrochemical performance of the manganese-based lithium iron phosphate positive electrode material. Summary of the invention

[0005] The purpose of the present invention is to provide a surface-modified manganese-based lithium iron phosphate positive electrode material to solve the following technical problems:

[0006] How to improve the electrochemical performance of manganese-based lithium iron phosphate positive electrode materials.

[0007] The purpose of the present invention can be achieved through the following technical solutions:

[0008] A surface-modified manganese-based lithium iron phosphate positive electrode material comprises the following components in parts by weight: 95-100 parts of lithium manganese iron phosphate and 2-3 parts of a multi-doped carbon composite; wherein the chemical formula of the lithium manganese iron phosphate is LiMn (1-X) Fe X PO4, 0.95≥X≥0.8; the multi-doped carbon composite is doped with fluorine, sodium and silver elements.

[0009] Preferably, the positive electrode material includes 98 parts of raw materials for preparing lithium manganese iron phosphate and 2.5 parts of multi-doped carbon composite;

[0010] Preferably, X=0.9.

[0011] Furthermore, the preparation method of the multi-element doped carbon composite is: dissolving sodium hexafluorophosphate in a silver nitrate solution with a mass fraction of 35%-50% and mixing them evenly to obtain a mixed solution, adding a carbon source to the mixed solution, and forming a solution containing the multi-element doped carbon composite after ultrasonic mixing; wherein the mass ratio of sodium hexafluorophosphate, silver nitrate and carbon source is 1:1:(10-12).

[0012] Preferably, the mass ratio of sodium hexafluorophosphate, silver nitrate and carbon source is 1:1:11.

[0013] In this process, sodium hexafluorophosphate contains fluorine and sodium elements, and silver nitrate contains silver element. After ultrasonic mixing, sodium hexafluorophosphate and silver nitrate are evenly distributed in the carbon source to form a multi-doped carbon complex doped with fluorine, sodium and silver elements.

[0014] Furthermore, the carbon source is an organic carbon source; the organic carbon source includes any one or more of sucrose, polyaniline, nanocarbon material, and glucose;

[0015] Preferably, the organic carbon source is polyaniline.

[0016] Furthermore, the LiMn (1-X) Fe X The raw materials for preparing PO4 include lithium source, manganese source, iron source and phosphorus source;

[0017] Furthermore, the manganese source includes one or more of manganese oxides (MnO2, MnO3, MnO7), manganese salts (MnC2O4, MnSO4, Mn(NO3)2, etc.); preferably, the manganese source is MnC2O4.

[0018] Furthermore, the lithium source includes one or more of lithium carbonate (Li2CO3), lithium hydroxide (LiOH), lithium acetate (CH3COOLi), lithium phosphate (Li3PO4), and lithium dihydrogen phosphate (LiH2PO4). Preferably, the lithium source is Li2CO3.

[0019] Furthermore, the iron source includes one or more of iron oxides (FeO, Fe2O3, Fe3O4), iron salts (FeCl3, Fe2(SO4)3, Fe(NO3)3); preferably, the iron source is FeCl3.

[0020] Furthermore, the phosphorus source includes one or more of phosphoric acid (H3PO4), ammonium phosphate ((NH4)3PO4), and diammonium phosphate (NH4H2PO4); preferably, the phosphorus source is H3PO4.

[0021] In a second aspect, the present invention further discloses a method for preparing the surface-modified manganese-based lithium iron phosphate positive electrode material as described above, comprising the following steps:

[0022] The first step is to follow LiMn (1-X) Fe X The molar mass ratio of each element in PO4 is as follows: lithium source, manganese source, iron source and phosphorus source are added into a ball mill together, the ball-to-material ratio is 20:1, and the ball mill is performed at 450-550rpm for 10-12h. During the ball milling process, a solution containing a multi-element doped carbon composite is added in small amounts and multiple times to fully mix the multi-element doped carbon composite and the raw material for preparing lithium manganese iron phosphate. After the ball milling is completed, a mixed slurry is obtained;

[0023] The second step is to place the mixed slurry in a vacuum drying oven and dry it at 80-120° C. for 12-16 hours to obtain a manganese-based lithium iron phosphate precursor;

[0024] The third step is to preheat the manganese-based lithium iron phosphate precursor at 300°C for 2 hours under inert gas protection, then heat it to 650-700°C at a heating rate of 5-8°C / min, and keep it at 650-700°C for 5-6 hours. After cooling to room temperature, grind it into powder to obtain a manganese-based lithium iron phosphate positive electrode material.

[0025] Beneficial effects of the present invention:

[0026] 1. During the preparation process, when ball-milling the raw materials of lithium manganese iron phosphate, the multi-component doped carbon composite is added thereto in small amounts and multiple times to fully mix the multi-component doped carbon composite with the raw materials for preparing lithium manganese iron phosphate, thereby improving their compatibility and making the mixed slurry more homogeneous, thereby improving the quality of the material and promoting its electrochemical performance.

[0027] 2. During the calcination of the manganese-based lithium iron phosphate precursor, the carbon source is carbonized to form a carbon coating layer, and the manganese-based lithium iron phosphate precursor is uniformly coated by the multi-doped carbon composite; the sodium hexafluorophosphate and silver nitrate in the multi-doped carbon composite are thermally decomposed under high temperature. Since the decomposition temperature of sodium hexafluorophosphate is higher than that of silver nitrate, the sodium hexafluorophosphate is first thermally decomposed to generate phosphorus fluoride gas and compound sodium fluoride, and the phosphorus fluoride escapes from the carbon coating layer to form a number of ultrafine interconnected pores on the primary carbon coating layer, and the silver element produced by the subsequent decomposition of the silver nitrate is embedded in the pores to form a network-like silver skeleton, and sodium fluoride is attached to the surface of the silver skeleton. After the thermal decomposition of the multi-doped carbon composite is completed, the formation of the carbon coating layer has not yet ended, so in the subsequent carbonization process, the formed carbon layer will bury the silver skeleton, and the silver skeleton is located inside the carbon layer, and its surface still presents a smooth carbon layer; the internal silver skeleton can improve the strength of the carbon coating layer on the one hand and prevent the escape of manganese ions, and on the other hand, the resistance of silver is extremely small, which will reduce the adverse effect of the carbon layer on the impedance of the positive electrode material, thereby improving its electrochemical performance.

[0028] 3. The sodium fluoride attached to the surface of the silver skeleton contains fluorine and sodium elements. First of all, fluorine has a strong electronegativity and can form stable chemical bonds with the carbon coating and other elements, thereby improving the structural stability of the material. The introduction of fluorine can also reduce safety hazards such as thermal runaway during the use of the battery, and improve the thermal stability and safety of the battery; the doping of sodium elements can improve its cycle reversibility, increase the reversible capacity, improve the sodium ion diffusion kinetics, etc., thereby improving the electrochemical properties of the positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] The present invention will be further described below in conjunction with the accompanying drawings.

[0030] Figure 1 It is a charge transfer resistance curve of the battery of lithium iron manganese phosphate positive electrode material prepared in Examples 1-3 of the present invention and Comparative Examples 1-4;

[0031] Figure 2 It is a capacity retention rate curve diagram of batteries of lithium manganese iron phosphate positive electrode materials prepared in Examples 1-3 of the present invention and Comparative Examples 1-4. DETAILED DESCRIPTION

[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] Preparation Example 1

[0034] Preparation of multi-element doped carbon composites: Add 10 g of sodium hexafluorophosphate into a beaker containing 25 g of 40% by mass silver nitrate solution and stir evenly to obtain a mixed solution, add 110 g of polyaniline as a carbon source to the mixed solution, stir evenly and then transfer to an ultrasonic mixer, and ultrasonically mix at 80 kHz for 40 minutes to obtain a solution containing the multi-element doped carbon composite.

[0035] Comparative Preparation Example 1

[0036] Preparation of carbon-doped composites: 10 g of sodium hexafluorophosphate was added to a beaker containing 25 g of deionized water and stirred evenly, and then 110 g of polyaniline was added as a carbon source. After stirring evenly, the mixture was transferred to an ultrasonic mixer and ultrasonically mixed at 80 kHz for 40 min to obtain a solution containing a carbon-doped composite.

[0037] Comparative Preparation Example 2

[0038] Preparation of carbon-doped composites: 110 g of polyaniline as a carbon source was added into a beaker containing 25 g of a 40% by mass silver nitrate solution and stirred evenly. After stirring evenly, the mixture was transferred into an ultrasonic mixer and ultrasonically mixed at 80 kHz for 40 min to obtain a solution containing a carbon-doped composite.

[0039] Example 1

[0040] According to LiMn 0.1 Fe 0.9 The molar mass ratio of each element in PO4 is as follows: 98 g of Li2CO3, MnC2O4, FeCl3 and H3PO4 are added to a ball mill with a ball-to-material ratio of 20:1. The ball mill is performed at 500 rpm for 11 hours. During the ball milling process, the solution containing the multi-doped carbon composite prepared in Preparation Example 1 is added in 5 times, and 0.5 g of the multi-doped carbon composite is added each time. After the ball milling, a mixed slurry is obtained; the mixed slurry is placed in a vacuum drying oven and dried at 100°C for 14 hours to obtain a manganese-based lithium iron phosphate precursor; the manganese-based lithium iron phosphate precursor is transferred to a sintering furnace, heated at 300°C for 2 hours under helium protection, and then heated to 680°C at a heating rate of 6°C / min, and kept at this temperature for 5.5 hours. After the end, it is cooled to room temperature, and then transferred to a grinder and ground into powder to obtain a manganese-based lithium iron phosphate positive electrode material.

[0041] Example 2

[0042] According to LiMn 0.2 Fe 0.8The molar mass ratio of each element in PO4 is as follows: a total of 95 g of Li2CO3, MnC2O4, FeCl3 and H3PO4 are added to a ball mill with a ball-to-material ratio of 20:1, and the ball mill is performed at 450 rpm for 12 hours. During the ball milling process, the solution containing the multi-doped carbon composite obtained in Preparation Example 1 is added in 5 times, and 0.4 g of the multi-doped carbon composite is added each time. After the ball milling is completed, a mixed slurry is obtained; the mixed slurry is placed in a vacuum drying oven and dried at 80°C for 16 hours to obtain a manganese-based lithium iron phosphate precursor; the manganese-based lithium iron phosphate precursor is transferred to a sintering furnace, heated at 300°C for 2 hours under helium protection, and then heated to 650°C at a heating rate of 5°C / min, and kept at this temperature for 6 hours. After the end, it is cooled to room temperature, and then transferred to a grinder and ground into powder to obtain a manganese-based lithium iron phosphate positive electrode material.

[0043] Example 3

[0044] According to LiMn 0.05 Fe 0.95 The molar mass ratio of each element in PO4 is as follows: 98 g of Li2CO3, MnC2O4, FeCl3 and H3PO4 are added to a ball mill with a ball-to-material ratio of 20:1. The ball mill is performed at 550 rpm for 10 hours. During the ball milling process, the solution containing the multi-doped carbon composite prepared in Preparation Example 1 is added in 5 times, and 0.6 g of the multi-doped carbon composite is added each time. After the ball milling, a mixed slurry is obtained; the mixed slurry is placed in a vacuum drying oven and dried at 120°C for 12 hours to obtain a manganese-based lithium iron phosphate precursor; the manganese-based lithium iron phosphate precursor is transferred to a sintering furnace, heated at 300°C for 2 hours under helium protection, and then heated to 700°C at a heating rate of 8°C / min, and kept at this temperature for 5 hours. After the end, it is cooled to room temperature, and then transferred to a grinder and ground into powder to obtain a manganese-based lithium iron phosphate positive electrode material.

[0045] Comparative Example 1

[0046] Compared with Example 1, the only difference is that the solution containing the multinary doped carbon composite prepared in Preparation Example 1 is replaced by the solution containing the carbon doped composite in Comparative Preparation Example 1, and other conditions are exactly the same, and finally a manganese-based lithium iron phosphate positive electrode material is prepared.

[0047] Comparative Example 2

[0048] Compared with Example 1, the only difference is that the solution containing the multi-doped carbon composite prepared in Preparation Example 1 is replaced by the solution containing the carbon-doped composite in Comparative Preparation Example 2, and the other conditions are exactly the same, and finally a manganese-based lithium iron phosphate positive electrode material is prepared.

[0049] Comparative Example 3

[0050] Compared with Example 1, the only difference is that the multinary doped carbon composite prepared in Preparation Example 1 is replaced by polyaniline, and other conditions are exactly the same, and finally a manganese-based lithium iron phosphate positive electrode material is prepared.

[0051] Comparative Example 4

[0052] According to LiMn 0.1 Fe 0.9 The molar mass ratio of each element in PO4 is as follows: 98 g of Li2CO3, MnC2O4, FeCl3 and H3PO4 are added to a ball mill together, and 10 mL of ethanol is added for dispersion. The ball-to-material ratio is 20:1. The ball mill is performed at 500 rpm for 11 hours. After the ball milling is completed, a mixed slurry is obtained. The solution containing the multi-doped carbon composite prepared in Preparation Example 1 is added to the mixed slurry and stirred evenly, wherein the multi-doped carbon composite is 2.5 g. The mixture is then placed in a vacuum drying oven and dried at 100 ° C for 14 hours to obtain a manganese-based lithium iron phosphate precursor; the manganese-based lithium iron phosphate precursor is transferred to a sintering furnace, heated at 300 ° C for 2 hours under helium protection, and then heated to 680 ° C at a heating rate of 6 ° C / min, and kept at this temperature for 5.5 hours. After the end, it is cooled to room temperature, and then transferred to a grinder and ground into powder to obtain a manganese-based lithium iron phosphate positive electrode material.

[0053] The manganese-based lithium iron phosphate positive electrode materials obtained in Examples 1-3 and Comparative Examples 1-4 were respectively made into batteries for testing of electrochemical properties. The preparation method is: 90g of manganese-based lithium iron phosphate positive electrode material, 5g of Super-P, and 5g of polyvinylidene fluoride are mixed evenly, and then 200g of N-methylpyrrolidone solvent is added, and mixed evenly to obtain a black slurry. The aluminum foil is placed in a coating machine, and the black slurry is poured in. After evenly coating, it is transferred to an oven and dried at 40°C for 4h. Then, the dried aluminum foil is placed in a punching machine, and several pole pieces containing active substances are punched out and weighed. The pole pieces are placed in a drying bottle, and transferred to a vacuum drying oven and dried at 110°C for 6h. Finally, they are assembled into button batteries in a vacuum glove box.

[0054] Then, the prepared button battery was subjected to electrochemical performance tests, its charge transfer resistance was tested using an electrochemical workstation, and its capacity retention rate was tested using a constant current-constant voltage charge-discharge method. Figure 1-2 The test results are listed in Table 1. Table 1 is as follows:

[0055]

[0056] By analyzing the data in Table 1, it can be seen that the batteries made of the manganese-based lithium iron phosphate positive electrode materials obtained in Examples 1-3 have significantly lower charge transfer resistance than those of Comparative Examples 1-4, which means that their electron migration rate is faster, while the capacity is significantly higher, which means that their rate performance is better; based on this, it can be seen that the surface-modified manganese-based lithium iron phosphate positive electrode material of the present invention has stronger electrochemical properties.

[0057] Specifically, compared with Example 1, the electrochemical performance of the manganese-based lithium iron phosphate positive electrode material prepared in Comparative Example 1 is worse, indicating that the addition of silver nitrate to the multi-doped carbon composite can reduce the charge transfer resistance and improve the capacity retention rate; compared with Example 1, the electrochemical performance of the manganese-based lithium iron phosphate positive electrode material prepared in Comparative Example 2 is worse, indicating that the addition of sodium hexafluorophosphate to the multi-doped carbon composite can reduce the charge transfer resistance and improve the capacity retention rate; compared with Example 1, the electrochemical performance of the manganese-based lithium iron phosphate positive electrode material prepared in Comparative Example 3 is worse, indicating that the multi-doped carbon composite can reduce the charge transfer resistance and improve the capacity retention rate; compared with Example 1, the electrochemical performance of the manganese-based lithium iron phosphate positive electrode material prepared in Comparative Example 4 is worse, but still higher than Comparative Examples 1-3, which indicates that the combination of the multi-doped carbon composite and the preparation method of multiple additions during grinding can reduce the charge transfer resistance and improve the capacity retention rate.

[0058] The above is a detailed description of an embodiment of the present invention, but the content is only a preferred embodiment of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.

Claims

1. A surface-modified manganese-based lithium iron phosphate positive electrode material, characterized in that: The method comprises the following components in parts by weight: 95-100 parts of raw materials for preparing lithium manganese iron phosphate and 2-3 parts of multi-element doped carbon composite; The chemical formula of the lithium iron manganese phosphate is LiMn (1-X) Fe X PO4, where 0.95 ≥ X ≥ 0.8; The doping elements in the multi-element doped carbon composite include fluorine, sodium and silver; The preparation method of the multi-element doped carbon composite is as follows: sodium hexafluorophosphate is dissolved in a silver nitrate solution and mixed evenly to obtain a mixed solution, a carbon source is added to the mixed solution, and ultrasonic mixing is performed to form a solution containing the multi-element doped carbon composite; The preparation method of the surface-modified manganese-based lithium iron phosphate positive electrode material comprises the following steps: The first step is to follow LiMn (1-X) Fe X The molar mass ratio of each element in PO4 is to add the lithium source, manganese source, iron source and phosphorus source together into a ball mill for ball milling. During the ball milling process, a solution containing a multi-component doped carbon composite is added in small amounts and multiple times. After the ball milling is completed, a mixed slurry is obtained; The second step is to place the mixed slurry in a vacuum drying oven and dry it at 80-120° C. for 12-16 hours to obtain a manganese-based lithium iron phosphate precursor; The third step is to preheat the manganese-based lithium iron phosphate precursor at 300°C for 2 hours under inert gas protection, then raise the temperature to 650-700°C, and keep it at 650-700°C for 5-6 hours. After cooling to room temperature, grind it into powder to obtain a manganese-based lithium iron phosphate positive electrode material.

2. The surface-modified manganese-based lithium iron phosphate positive electrode material according to claim 1, characterized in that: The carbon source is an organic carbon source, and the organic carbon source includes any one or more of sucrose, polyaniline, nanocarbon material, and glucose.

3. The surface-modified manganese-based lithium iron phosphate positive electrode material according to claim 1, characterized in that: In the multi-doped carbon composite, the mass ratio of the sodium hexafluorophosphate, silver nitrate and carbon source is 1:1:(10-12).

4. The surface-modified manganese-based lithium iron phosphate positive electrode material according to claim 1, characterized in that: The mass fraction of the silver nitrate solution is 35%-50%.

5. The surface-modified manganese-based lithium iron phosphate positive electrode material according to claim 1, characterized in that: The LiMn (1-X) Fe X The raw materials for preparing PO4 include lithium source, manganese source, iron source and phosphorus source.

6. The surface-modified manganese-based lithium iron phosphate positive electrode material according to claim 5, characterized in that: The manganese source includes one or more of manganese oxides and manganese salts; The lithium source includes one or more of lithium carbonate, lithium hydroxide, lithium acetate, lithium phosphate, and lithium dihydrogen phosphate; The iron source includes one or more of iron oxides and iron salts; The phosphorus source includes one or more of phosphoric acid, ammonium phosphate, and diammonium phosphate.

7. The surface-modified manganese-based lithium iron phosphate positive electrode material according to claim 1, characterized in that: In the first step, a planetary ball mill is used for ball milling, with a ball-to-material ratio of 20:1, a ball milling speed of 450-550 rpm, and a ball milling time of 10-12 h.

8. The surface-modified manganese-based lithium iron phosphate positive electrode material according to claim 1, characterized in that: In the third step, after preheating, the temperature is increased to 650-700°C at a heating rate of 5-8°C / min.

Citation Information

Patent Citations

  • Monatomic doped lithium manganese iron phosphate composite material and preparation method and application thereof

    CN116169262A

  • Multi-element trace co-doped lithium iron phosphate / carbon composite positive electrode material as well as preparation method and application thereof

    CN116404140A